Knowledge of Breast Cancer Among Urban Women in the South of Peninsular Malaysia - Lim, Phui Yee; Yusuf, Azlina (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: : Breast cancer (BC) is the most commonly diagnosed cancer globally and it is the leading cause of cancer mortality in Malaysian women. Increasing women knowledge of BC and breast self-examination (BSE) leads to increased compliance in early diagnosis and treatment. This study aims to determine the level of knowledge on BC and its association with socio-demographic characteristics among urban women. Methods: A cross-sectional study was conducted among 270 urban women in the South of Peninsular Malaysia using the adapted Breast Cancer Awareness Measure. Data were analyzed through SPSS software version 26.0. Results: Of the participants, 53.7% (n=145) had poor knowledge of BC warning signs, 50.7% (n=137) of BSE and 55.6% (n=150) of risk factors. High education was associated with better BC knowledge on warning signs (p=0.006) and risk factors (p=0.048). Chinese women have poor BC knowledge on warning signs (p=0.005) and BSE (p<0.001) than other ethnicities. Age (p=0.024) and marital status (p=0.028) were statistically significant with BC knowledge on breast self-examination (BSE) while family history of BC (p=0.019) and duration of seeking medical advice (p=0.041) were associated with BC knowledge on the risk factor. Conclusion: The findings of this study may give insight into effective health education strategies for urban women concerning breast cancer awareness.